Original paperAssessment of the sensory threshold in patients with atopic dermatitis and psoriasis - Krzyżanowska, Magdalena; Muszer, Katarzyna; Chabowski, Konrad; Reich, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Atopic dermatitis (AD) and psoriasis are chronic inflammatory skin diseases frequently accompanied by itching. The exact pathogenesis of dermatological pruritus remains unknown, but it is believed that altered skin innervation may play a role. Aim : The assessment of the sensory threshold in AD and psoriasis in relation to pruritus experienced by patients. Material and methods : A total of 18 subjects with AD, 20 with psoriasis and 49 healthy controls were exposed to alternating current generated by the current source. A selected preset of current frequencies (ranging from 5 Hz to 2000 Hz) allowed a selective stimulation of different nerve endings (Aβ, Aδ and C-type). Pruritus severity was measured with visual analogue scale (VAS) and an itch questionnaire developed in house. All results were analyzed statistically. Results : Sensory thresholds within the uninvolved skin of AD or psoriasis patients were significantly higher than in healthy volunteers (p 0.05). Similarly, sensory thresholds within the diseased skin of AD or psoriasis were significantly higher than in the normal skin (p < 0.01), and patients with psoriasis had also a significantly higher threshold than AD individuals (p < 0.05). The sensory threshold inversely correlated with pruritus severity in AD and psoriasis and the highest correlation was found for 5 Hz frequency predominantly stimulating C fibers (VAS: R = –0.32, p < 0.05; pruritus questionnaire: R = 0.54, p < 0.001). Conclusions : Evaluation of the sensory threshold may be a valuable tool for pruritus assessment, but further studies are still warranted.